Proteomic and metabolomic analysis of platelet related samples reveals energy metabolism disorders in hepatocellular carcinoma - Xuelian Ruan; Zuojian Hu; Fenglin Shen; Yongling Chen; Ziqing Zhong; Guiyong Ou; Xing Luo; Xue Qin; Huabing Wang (Journal of Translational Medicine)
Abstract Background Hepatocellular carcinoma (HCC) is one of the most prevalent cancers in the world. Platelets play an important role in thrombosis, inflammation, and tumors. This study tries to gain a pathway-based view of platelets-related samples for understanding metabolic disorders and identifying novel biomarkers in HCC by combining proteomics and metabolomics. Methods Forty-five HCC patients and thirty-four healthy controls were included in the study. We performed label-free proteomic analysis of platelets from 14 HCC patients and 14 healthy controls. Target metabolomics analysis was performed on platelet-rich plasma (PRP) from 31 HCC patients and 20 healthy controls. Western blotting was performed to validate the results of proteomics. Glutamine (Gln) deprivation assay was conducted to evaluate the effect of Gln metabolism on the platelet-induced proliferation, migration, and invasion of HCC cells. Results Proteomics analysis revealed dysregulation of platelets function and energy metabolism in HCC patients compared with healthy controls. Target metabolomics analysis showed widespread dysregulation of amino acids in HCC patients. Integrating analysis of differential proteins and metabolites revealed five significant dysregulated pathways in HCC patients. Western blotting validation results showed that the expression levels of SDHB, CISY, and FUMH were significantly up-regulated in HCC patients compared to healthy controls, which was consistent with the proteomics findings. Biological function revealed that Gln-free weakens the ability of platelet-induced proliferation, migration, and invasion of HCC cells. Diagnostic evaluation demonstrated superior discriminatory power for SDHB (AUC = 0.929) compared to alpha-fetoprotein (AFP) in platelet proteomics. Furthermore, a triad of tricarboxylic acid cycle intermediates (succinic acid, fumaric acid, and malic acid) significantly enhanced the AUC, specificity, and sensitivity of distinguishing HCC patients from healthy controls compared to AFP. Conclusions Through multi-omics characterization of platelets-related samples, the network of altered proteins and metabolites provides a comprehensive view of altered metabolism in the peripheral circulation of HCC patients. Gln deprivation inhibited the ability of platelet-induced malignant biology function in HCC cells. Collectively, proteomics and metabolomics provide evidence for possible future non-invasive or minimally invasive biopsies for patients with HCC.